A recovery-oriented peer provider (ROPP) work-role model and prototype measure. Issue 4 (2nd October 2017) - Moran, Galia S.
ABSTRACT: Peer providers (PPs) are essential in recovery-oriented mental health (MH) services but are often disempowered and their role is misunderstood. The author aimed to enhance the PP work role by (1) conceptualizing PPs' optimal views and experiences of their work role and (2) presenting a prototype self-report measure to assess PP optimal expression in MH services. The author analyzed optimal work-role experiences described by 25 PPs working in diverse MH settings using a grounded theory approach. To develop the measure the author employed the Delphi method with another group of eight experienced PPs. The author defines a recovery-oriented peer provider (ROPP) work-role model involving three domains: basic skills, peer-oriented relationships, and role motivations. Based on the ROPP model, the author developed a prototype 38-item self-report scale. The scale gauges multilevel PP processes: providing support via lived experience; communicating the consumer-voice/lived-experience to MH staff; identifying with and being motivated by the PP role. ROPP characterizes PPs' use of lived experience within eye-level relationships in traditional MH services. ROPP is relevant to diverse MH services interested in developing a recovery orientation. The ROPP scale, once psychometrically validated, can assess PPs optimal expression in MH services, and can already be used for self- assessment and organizational consultation.